Factors Associated With Multimorbidity Patterns in Older Adults in England: Findings From the English Longitudinal Study of Aging (ELSA). (1st December 2019) - Nguyen, Hai; Chua, Kia-Chong; Dregan, Alexandru; Vitoratou, Silia; Bayes-Marin, Ivet; Olaya, Beatriz; Prina, A. Matthew
Objective: We aimed to identify the patterns of multimorbidity in older adults and explored their association with sociodemographic and lifestyle risk factors.Method: The sample included 9, 171 people aged 50+ from Wave 2 of the English Longitudinal Study of Aging (ELSA). Latent Class Analysis (LCA) was performed on 26 chronic diseases to determine clusters of common diseases within individuals and their association with sociodemographic and lifestyle risk factors.Result: Three latent classes were identified: (a) a cardiorespiratory/arthritis/cataracts class, (b) a metabolic class, and (c) a relatively healthy class. People aged 70 to 79 were 9.91 times (95% Confidence Interval [CI] = [5.13, 19.13]) more likely to be assigned to the cardiorespiratory/arthritis/cataracts class, while regular drinkers and physically inactive people were 0.33 times (95% CI = [0.24, 0.47]) less likely to be assigned to this class.Conclusion: Future research should investigate these patterns further to gain more insights into the needs of people with multimorbidity.